Three phase UPFC regulator with reduced bus capacitance for solar PV application system - Uddin, Md. Nasir; Rashid, Muhammad Mahbubur; Nithe, N. A. (Global Journals Inc. (USA), 2016)
This paper, propose a A Three-Phase Reduced DC Bus Capacitance Unified Power Flow Controller (UPFC) for Low Voltage (LV) distribution Networks with High Photovoltaic (PV) penetrations. The device is shown capable of voltage regulating and correcting phase unbalance voltages that can be produced by high levels of distributed photovoltaic (PV) generation. The device is also capable of Power factor improvement (PFI) and correction, regulating the zero, positive and negative sequence voltage in LV distribution Networks and neutral or zero sequence current compensation. Instantaneous reactive power theory shows The power of DC Bus capacitor will fluctuate at twice mains frequency during unbalanced operation. The Real and Instantaneous power balance of Unified Power Flow Controller (UPFC) can be maintained by allowing the shunt input converter to draw a small negative and positive sequence current. The Instantaneous Power balance with negative sequence current allows a hundred-fold reduction in the value of DC bus capacitance which allows long life polypropylene or ceramic capacitors to replace of electrolytic capacitor in this application.